PROBLEMS OF INFORMATION AND ANALYTICAL PROVISION OF BUSINESS ACTIVITIES UNSHADOWING IN UKRAINE - DYMCHENKO, Olena; SMACHYLO, Valentyna; TARARUIEV, Iurii (Herald of Khmelnytskyi National University. Economic sciences, 2023)
According to the results of the systematization and analysis of the problems of information and analytical support of the of business activity unshadowing in Ukraine, it was determined that these problems are interconnected, and ignoring them significantly complicates the unshadowing process.  It was found out that the peculiarities of shadow activity require the state to create proper conditions for the voluntary exit of entrepreneurs from the shadow sector of the economy. At the same time, the legalization of activity should be beneficial for entrepreneurs. The article emphasizes that the change in the status of entrepreneurs should be properly recorded by state bodies, which will lead to the accumulation of primary information and allow determining the success criteria of unshadowing, the ratios for the calculation of which are given above. To simplify the analysis, the indicator of tax revenues per legalized business entity is presented in the form of a two-factor multiplicative model, which will allow provide factor analysis of unshadowing processes and improve the given model by adding factor indicators. The final result of the article is the formulation of the stages of information and analytical support for the unshadowing of entrepreneurial activity. Prospective areas of research into the problems of information and analytical support for the unshadowing of entrepreneurial activity include: substantiation of practical proposals for motivating entrepreneurs to exit the shadow sector of the economy through the use of tax discounts, debt restructuring, etc.; clarification of the list of indicators that can be considered criteria for the success of entrepreneurial activity unshadowing; application of mathematical methods to substantiate hypotheses regarding the size and changes of the shadow sector of the economy of Ukraine.
Keywords: shadow activities; unshadowing; entrepreneurial activity; information and analytical support of unshadowing; unshadowing conditions; success criteria of unshadowing